Pengembangan LKPD Bermuatan Nilai Kreatif Melalui Model Project Based Learning Pada Materi Larutan Elektrolit dan Non Elektrolit - Molani Paulina Hasibuan; Ratih Permana Sari; Santi Santi; Nur Azizah Lubis (Jurnal Penelitian Pendidikan IPA, 2023)
Student worksheets give students the opportunity to participate in hands-on learning, discover strengths and learn from their mistakes. This research aims to produce student worksheets with creative values through the Project Based Learning model on electrolyte and non-electrolyte solution materials.Â  This research is a development research, the method used in this research is the R&D (Research and Development) method with the ADDIE model modified into ADD, namely Analysis, Design and Development. The instrument in this research is a needs questionnaire, media and material expert feasibility questionnaire, teacher response questionnaire and student response questionnaire. The results showed that chemistry teachers need student worksheets with creative values through the Project Based Learning model on the material of electrolyte and non-electrolyte solutions. The feasibility of student worksheets was obtained at 77.08% with a feasible category, the practicality was in the very practical category with an average score of 89.50% and the attractiveness of student worksheets in the very attractive category with an average score of 89.97%. So it can be concluded that the developed creative value-loaded student worksheets is feasible to use in learning.